NOVICE EFL TEACHERS’ CHALLENGES AND STRATEGIES IN TECHNOLOGY-MEDIATED SPEAKING INSTRUCTION IN WEST KALIMANTAN - Septiana, Dita; Sari, Riski Amrina (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT This study examines the challenges encountered by novice EFL teachers in West Kalimantan when conducting speaking instruction through technology-mediated environments. Although digital tools have become increasingly integrated into classroom practices, many beginning teachers still struggle to use them effectively, particularly for interactive skills such as speaking. Using a qualitative descriptive design, data were collected through interviews with novice teachers from several senior high schools. The findings reveal three main challenges: limited digital pedagogical competence, difficulty sustaining student engagement in online speaking tasks, and inconsistent technological access among learners. Nevertheless, teachers employed several adaptive strategies, including simplifying digital tools, providing structured speaking models, using multimodal platforms such as voice notes and video tasks, and offering additional support outside scheduled class hours. These strategies helped sustain communication and support students’ speaking development. The study concludes that novice teachers require more extensive preparation in digital pedagogy and ongoing institutional assistance to manage technology-based speaking instruction effectively. Strengthening technology training in teacher education programs is recommended to enhance teachers’ confidence and competence in technology-supported language teaching. ABSTRAK Studi ini meneliti tantangan yang dihadapi oleh guru EFL pemula di Kalimantan Barat ketika melakukan pengajaran berbicara melalui lingkungan yang dimediasi teknologi. Meskipun alat digital semakin terintegrasi ke dalam praktik kelas, banyak guru pemula masih kesulitan menggunakannya secara efektif, khususnya untuk keterampilan interaktif seperti berbicara. Dengan menggunakan desain deskriptif kualitatif, data dikumpulkan melalui wawancara dengan guru pemula dari beberapa sekolah menengah atas. Temuan menunjukkan tiga tantangan utama: kompetensi pedagogis digital yang terbatas, kesulitan mempertahankan keterlibatan siswa dalam tugas berbicara daring, dan akses teknologi yang tidak konsisten di antara para pembelajar. Meskipun demikian, guru menerapkan beberapa strategi adaptif, termasuk menyederhanakan alat digital, menyediakan model berbicara terstruktur, menggunakan platform multimodal seperti catatan suara dan tugas video, dan menawarkan dukungan tambahan di luar jam kelas yang dijadwalkan. Strategi-strategi ini membantu mempertahankan komunikasi dan mendukung perkembangan berbicara siswa. Studi ini menyimpulkan bahwa guru pemula membutuhkan persiapan yang lebih luas dalam pedagogi digital dan bantuan kelembagaan yang berkelanjutan untuk mengelola pengajaran berbicara berbasis teknologi secara efektif. Penguatan pelatihan teknologi dalam program pendidikan guru direkomendasikan untuk meningkatkan kepercayaan diri dan kompetensi guru dalam pengajaran bahasa yang didukung teknologi.